Effects of water-bath stunning on the death of poultry and myofiber apoptosis - Shahdan, Intan Azura; Rahman, Mohammad Tariqur (2014)
According to the Islamic slaughtering guidelines, swift slaughtering is one of the criteria for good slaughter. In this study, stunning effectiveness in halal poultry meat production was analysed in response to the time needed for the chickens to become insensible upon neck cutting (Td) and the induction of myofiber apoptosis. Td was recorded using a stopwatch timer, which started at the point of neck cutting and stopped when there were absence of wing flapping, pupil reflex, comb pinching response and heart beat in the chickens. In total, 49 chicken broilers (body weight of 2.17 ± .24 kg) were sacrificed without stunning and with pre-slaughter stunning, using a constant voltage stunner where the current varied between 7.2 to 124.3 mA. The current applied during stunning was found to have no effect on Td. Meat samples from stunned and unstunned chickens were preserved in formalin within 30 min postmortem and apoptotic activity of the muscles were analysed using TUNEL assay and immunohistochemistry. Number of apoptotic myonuclei did not vary among stunned and unstunned meat. Apoptosis inducing factor (AIF) and caspase 3 expressions were not induced in the meat samples of both stunned and unstunned groups at 1 d postmortem. Activations of AIF and caspase 3 lead to DNA fragmentation and apoptosis. Since the slaughtering process and stunning are associated with stress, the expression of 70 kDa-heat shock protein (Hsp70) was investigated. Moreover Hsp70 is also an inhibitor of apoptosis, by preventing the activation of AIF and apoptosome which stimulates caspase 3 activation. However, expression of Hsp70 was not induced in both stunned and unstunned groups. This could be due to the short-life span of Hsp70 in vivo, and the very low level of Hsp70 which was undetectable using the method in this study. More details will be shared during the presentation.